PARTISIPASI MAHASISWA KULIAH KERJA NYATA TEMATIK WIRA DESA (KKNT-WD) DALAM KEGIATAN MASYARAKAT - Puji Muniarty; Wulandari Wulandari; Nabila Putri Sakinah; Bambang Hermanto; Rifka Annisa (Lembaga Pengembangan, Penelitian dan Pengabdian Kepada Masyarakat Universitas Banten Jaya, 2021)
Real Work Lecture (KKN) is a community empowerment activity by students as a manifestation of the tridharma activities of higher education. Community service activities aim to enable students to implement science and technology as well as skills in the community so that they can become agents of change and sustainable development. The participation of KKN students in community activities plays an important role in the success of work program activities while at the KKN location. This participation can be demonstrated by being directly involved in several preparations for the 76th Independence Day of the Republic of Indonesia held by the Dodu Village Youth Organization. The Bima College of Economics (STIE) with its vision of